Work-life Integration and Mental Health Issues among Higher Education Staff - Siti Aisyah, Panatik; Errna Nadirah, Kamalulil; Junaidah, Yusof; Khairul Azmi, Ishak (UNIMAS Publisher, 2022)
The multiple roles and responsibilities assigned to staff members in public tertiary education have led to an imbalance of work and life interface, which eventually affected their mental health. Therefore, this study aims to examine the influence of work-life integration on mental health among staff who are working at a higher education institution in Johore, Malaysia. This study utilized a quantitative approach, in which a set of questionnaires was distributed through an online survey. A total of 137 respondents participated in this study. The data were analyzed using descriptive and inferential statistics via SPSS Version 26 and SmartPLS 3.0. The findings indicated that the level of work-to-life integration and life-to-work integration is ranked between moderate to high, and moderate to low, respectively. The level of mental health is indicated at a moderate level. This study also found that work-life integration has a significantly positive influence on mental health.